Enhancing STEAM Skills in Early Childhood through Contextual Learning - Violy, Agita (Akademika, 2024)
This research focuses on enhancing Science, Technology, Engineering, Art, Mathematics (STEAM) skills in early childhood education through contextual learning by incorporating field trips to automotive workshops. The aim is to address the problem of how to effectively enhance STEAM skills in young children by utilizing contextual learning through study visits to automotive workshops. The study adopts a qualitative descriptive approach with a case study method, focusing on 20 children aged 5–6 years at Raudhatul Athfal Muslimat, Mustikajaya, Bekasi. Data were collected through observation, interviews, and documentation to provide an in-depth understanding of the learning process and outcomes by having children complete worksheets and create a simple car automotive workshop project using loose parts. The results indicate that contextual learning in an automotive workshop significantly enhances children's STEAM skills through 7 sub-elements of learning outcomes based on the Merdeka Curriculum in the Foundation Phase, which aligns with Bloom's Taxonomy. This approach fosters critical 21st-century skills, including communication, collaboration, and problem-solving, by engaging children in real-world activities that connect theory with practice. The study concludes that integrating contextual learning into STEAM education provides a practical, effective, and innovative framework for fostering holistic child development, ensuring that children are better prepared to face future challenges in an increasingly complex world.